Study on compressive strength of bamboo (Guadua amplexifolia J. Presl) in San Jorge River basin, Colombia - Yiniva Camargo Caicedo; Jorge Augusto Montoya Arango; Ricardo Acosta Acosta (Results in Engineering)
Bamboo is a fast-growing plant commonly used to produce handicrafts, baskets, furniture, and other goods. Guadua amplexifolia J. Presl, a native woody bamboo species of Colombia, has been the subject of limited scientific research. This study conducted in the San Jorge River basin in Montelíbano (Córdoba) evaluated Guadua amplexifolia J. Presl's compressive strength to find its potential applications. Samples from four- and five-year-old bamboo culms were collected for analysis. The findings showed a positive correlation between the modulus of rupture and density. In contrast, the modulus of elasticity showed a weak positive correlation. It was seen that the predominant mode of compressive strength failure was type A (accounted for 66.7 %) in the samples tested. The mean value for the modulus of rupture was 43.1 x10−3 MPa, and the mean modulus of elasticity value was 1075.5 x10−3 MPa. Earlier studies reported lower calculated values for modulus of rupture and modulus of elasticity for G. amplexifolia J. Presl bamboo than other bamboo species.